Governance of territorial human capital: An attempt to develop a composite index in the SEMCs and the EACs - Mazzaourou, Abdeljalil; Chakir, Kamal (Technium Social Sciences Journal, 2023)
In neo-classical studies, we often speak of the concept of human capital. It is considered as a full-fledged component in the economic growth equation and is a barometer of the governance of countries vis-à-vis this component. As such, it has been the subject of much theoretical and empirical research. However, several approaches have been used to measure the territorial human capital stock in a country at a given time, which often biases the results obtained. Typically, we see measures that neglect the health dimension. In this essay, we have established a composite and synthetic indicator of macro-economic measures of territorial human capital integrating not only the educational dimension but also the health dimension in two groups of countries, in this case the Southern and Eastern Mediterranean Countries and the Emerging Asian Countries.